Quality Attributes of Cured and Smoked Chicken Legs Using Different Processing Methods : doi: 10.5958/2581-6616.2021.00007.4 - S., A.; R., A.; K, Sen; Fairoze, Nadeem; Muthukumar, M.; Naveena, B.M.; Reddy, G. V. Bhaskar (Journal of Meat Science, 2022)
Preliminary trials for processing cured and smoked chicken legs were conducted using variables like a method of treatment (dipping, dry curing, injection, and tumbling) and brine solution at different concentrations and optimized by evaluating the product by a sensory panel and calculating the residual nitrite content. The processing methods (T1- Injection and dipping (24 hours); T2- Injection and tumbling twice for 30 min with a gap of 20 min in between, and T3- Injection, tumbling for 20 min and dipping for 12 h) were adopted for the development of cured and smoked chicken legs and evaluated the quality of developed products. No significant differences in the pH of chicken legs are observed. The shear force value is significantly lower (P<0.05) in T1 and T3 as compared to T2. Residual nitrite was significantly less (P<0.05) in T3 as compared to T1 and T2. The T3 had significantly higher nitroso pigment (%) than T1 and T2. No significant differences were observed in proximate composition amongst different processing conditions of smoked chicken legs. In sensory evaluation, the T3 was rated higher in colour and overall acceptability score. It can be concluded that tumbling had a better effect on the development of cured and smoked chicken legs with superior quality attributes. Further, we can reduce the processing time by decreasing the dipping time in the brine solution.